Non-tariff and overall protection: evidence across countries and over time - Niu, Zhaohui; Liu, Chang; Gunessee, Saileshsingh; Milner, Chris (Springer, 2018)
This paper analyzes the evolution of the incidence and intensity of non-tariff measures (NTMs). It extends earlier work by measuring protection from NTMs over time from a newly available database and provides evidence on the evolution of NTMs. In particular, building on Kee, Nicita and Olarreaga (2009), this paper estimates the ad valorem equivalents (AVEs) of NTMs for 97 countries at the product level over the period 1997 to 2015. We show that the incidence and the intensity of NTMs were both increasing over this period, with NTMs becoming an even more dominant source of trade protection. We are also able to investigate the evolution of overall protection derived jointly fromtariffs and NTMs. The results show that the overall protection level, for most countries and products, has not decreased despite the fall in tariffs associated with multilateral, regional and bilateral trade agreements in recent decades. We also document an increase in overall trade protection during the recent 2008 financial crisis. Overall, this study sheds light on an under-researched aspect of trade liberalization: the proliferation and increase of NTMs.